Women and music in cross-cultural perspective - Koskoff, Ellen (University of Illinois Press, 1989)
This volume offers an introduction to the field of women, music and culture, examining the implications of gender upon music performance. The presentation focuses on women from many different countries, societies and historical periods, from the professional to the urban musician